A schistosomiasis health education intervention among rural Malawian school children : lessons learned - Bandawe, Chiwoza Rutendo (Department of Psychology, 2023)
This thesis is the product of a two-year intervention aimed at controlling the prevalence of schistosomiasis (Bilharzia), a parasitic disease, among school children in a rural area of11angochi District, Malawi between 1996 and 1998. The question this thesis addresses as its focus is, which degree of health education input is the most efficient in controlling schistosomiasis? Guided by the. empirically supported social psychology theories of reasoned action (Ajzen & Fishbein, 1980) and planned behaviour (Ajzen, 1991), three varying degrees of health education input were provided to three primary schools, in the Koche catchment area of Mangochi. Each school was randomly assigned a different input. One school received "minimum" input consisting of basic information provision through a brief talk given by a health professional. Another school was given the "medium" condition which was similar but had the addition of multimedia input to the school through peers in the form of clubs and the third school deemed the "maximum" condition had the addition of pupil interaction with the local community. The framework that guided the intervention was Green's PRECEDE-PROCEED model (Green & Kreuter, 1991). It was used to guide the planning, implementation and evaluation of the intervention. Qualitative and quantitative research methods were employed to assess the three schools pre and post intervention. Comparisons were made across the schools as well as within two of the schools, comparing members of Bilharzia clubs established with non-members. No significant differences were observed across the input conditions. However, a subsection of the participants, the school club members experienced the most positive shifts in knowledge, attitude, behavioural intention and practice, Reduction of the prevalence of the disease was dependent on ongoing medication. It is concluded that the most efficient health education input was intense weekly input through the formation of clubs othenNise a brief lecture has the same effect on knowledge and practice as multimedia campaigns. Intentions of the sample were predominantly under non-native control prompting recommendations for further culturally based research using discursive approaches.